Woman and goddess in Hinduism: reinterpretations and re-envisionings - Pintchman, Tracy (Palgrave Macmillan, 2011)
"Offering multilayered explorations of Hindu understandings of the Feminine, both human and divine, this book emphasizes theological and activist methods and aims over historical, anthropological, and literary ones. The contributors approach the Feminine in Hindu traditions from the standpoint of intersubjective construction via a method that can be termed dialexis. Here, dialexis refers to a form of intellectual engagement "across styles" that takes as its starting point an adequate accounting of contextualized signification. The diverse ways that cultures articulate themselves are rooted in lexical choices made in historical, geographical, and cultural contexts"--